Already have an account? Get multiple benefits of using own account!
Login in your account..!
Remember me
Don't have an account? Create your account in less than a minutes,
Forgot password? how can I recover my password now!
Enter right registered email to receive password!
Given f ( x ) = x2 - 2 x + 8 and g( x ) = √(x+ 6) evaluate f (3) and g(3)
Solution
Okay we've two function evaluations to do here and we've also obtained two functions so we're going to decide which function to employ for the evaluations. Here the key is to notice the letter that is in front of the parenthesis. For f(3) we will use the function f( x ) and for
g (3) .we will employ g ( x ) . In other terms, we just have to make sure that the variables match up.
Following are the evaluations for this part.
f(3) = (3)2 - 2 (3) +8 = 9 - 6 + 8 = 11
g(3) =√(3+6) =√9=3
f(x) = x3 - 9x + 3
Example : Use the quadratic formula to solve following equation. x 2 + 2x = 7 Solution Here the important part is to ensure that before we b
The second method of solving quadratics is square root property, If p 2 = d then p =±d There is a (potential
How would you solve this equation: 13x + 7 (-3x-1) = -63
how do i find the length of the sides of a right triangle
3x+y=-2 6x+2y=10
what is 8 14/10 in simplest form
Write the inverse function of: f(x)=4x-1
find the sum upto n terms of the following sequence 3+33+333+... n terms
x squred y+ x
Get guaranteed satisfaction & time on delivery in every assignment order you paid with us! We ensure premium quality solution document along with free turntin report!
whatsapp: +1-415-670-9521
Phone: +1-415-670-9521
Email: [email protected]
All rights reserved! Copyrights ©2019-2020 ExpertsMind IT Educational Pvt Ltd